Neuroprotection from protein misfolding in cerebral hypoperfusion concurrent with metabolic syndrome. A translational perspective - Bordet, Sofía; Luaces, Juan Pablo; Herrera, Maria Ines; Gonzalez, Liliana Mirta; Kobiec, Tamara; Perez-Lloret, Santiago; Otero-Losada, Matilde; Capani, Francisco (Frontiers in Neuroscience, 2023)
Based on clinical and experimental evidence, metabolic syndrome (MetS) and type 2 diabetes (T2D) are considered risk factors for chronic cerebral hypoperfusion (CCH) and neurodegeneration. Scientific evidence suggests that protein misfolding is a potential mechanism that explains how CCH can lead to either Alzheimer's disease (AD) or vascular cognitive impairment and dementia (VCID). Over the last decade, there has been a significant increase in the number of experimental studies regarding this issue. Using several animal paradigms and different markers of CCH, scientists have discussed the extent to which MetS or T2D causes a decrease in cerebral blood flow (CBF). In addition, different models of CCH have explored how long-term reductions in oxygen and energy supply can trigger AD or VCID via protein misfolding and aggregation. Research that combines two or three animal models could broaden knowledge of the links between these pathological conditions. Recent experimental studies suggest novel neuroprotective properties of protein-remodeling factors.In this review, we present a summarized updated revision of preclinical findings, discussing clinical implications and proposing new experimental approaches from a translational perspective. We are confident that research studies, both clinical and experimental, may find new diagnostic and therapeutic tools to prevent neurodegeneration associated with MetS, diabetes, and any other chronic non-communicable disease (NCD) associated with diet and lifestyle risk factors.